2021
DOI: 10.3233/jad-200991
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Crisis Effects on Caregiver Distress in Neurocognitive Disorder

Abstract: Background: The outbreak of the COVID-19 pandemic seems to have mental health implications for both people with neurocognitive disorder and their caregivers. Objective: The study aimed to shed light on relations between caregiver mental reaction to the pandemic and caregiver distress related to neuropsychiatric symptoms, memory impairment progression, and functional impairment of people with neurocognitive disorder during the period of confinement in Greece. Methods: The study included caregivers of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 28 publications
2
37
0
1
Order By: Relevance
“…Remarkably, during the SARS or MERS epidemics, neuropsychiatric symptoms have been reported in hospital workers and caregivers (11). A similar situation has been reported in hospital workers assisting COVID19 patients (12).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Remarkably, during the SARS or MERS epidemics, neuropsychiatric symptoms have been reported in hospital workers and caregivers (11). A similar situation has been reported in hospital workers assisting COVID19 patients (12).…”
Section: Introductionsupporting
confidence: 82%
“…The copyright holder for this preprint this version posted April 27, 2021. ; https://doi.org/10.1101/2021.04.23.21255973 doi: medRxiv preprint MERS epidemics, neuropsychiatric symptoms have been reported in hospital workers and caregivers (11). A similar situation has been reported in hospital workers assisting COVID19 patients (12). The COVID19 syndrome also compromises internal organs and apparatuses other than the nervous or cardiovascular systems, including the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 78%
“…The same study found that ICs of PWD with higher rates of resilience reported a significant increase in anxiety during the lockdown, suggesting that a pandemic can have a negative psychological effect even on mentally strong ICs. An additional study found that IC of PWD distress arose during the quarantine period, regardless of whether the care receiver’s neurocognitive symptoms changed ( Alexopoulos et al., 2021 ). This study also found increased IC anxiety symptoms were unrelated to the severity of their care receiver’s neurocognitive disorder.…”
Section: Resultsmentioning
confidence: 99%
“…IC’s distress during quarantine was influenced by memory deficits and neuropsychiatric symptoms ( Alexopoulos et al., 2021 ). Caregiver’s symptoms of depression and anxiety also increased as the length of time in isolation increased ( Mazzi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…For patients under home noninvasive ventilation (HMV) for chronic respiratory failure (CRF), confinement blocked access to elective procedures, such as routine follow-up visits dedicated to assessing efficacy of treatment and adequacy of settings, and compromised the feasibility of treatments provided at home such as rehabilitation or chest therapy. It also created anxiety not only among patients with chronic disorders but also among relatives, caregivers, and health-care workers [ 1 , 2 , 3 , 4 ] due to the high risk of infection but also because the activity of our public hospital was totally diverted to the care of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%